Graphene embedded surface plasmon resonance based sensor prediction model - Meshginqalam, B. (Springer New York LLC, 2016)
Exceptional optical and electrical characteristics of graphene based materials attract significant interest of the researchers to develop sensing center of surface plasmon resonance (SPR) based sensors by graphene application. In this research carrier density variant in the form of conductance gradient on graphene based SPR sensor response is modeled. The molecular properties such as electro-negativity, molecular mass, effective group number and effective outer shell factor are engaged. In addition each factor effect in the cumulative carrier variation is explored analytically. The refractive index shift equation based on these factors is defined and related coefficients are proposed. Finally a semi-empirical model for interpretation of changes in SPR curve is suggested and tested for some organic molecules.